Economic Development and Climate Change - An Indian Perspective - Mehta, Jayashree F. (Prabandhan: Indian Journal of Management, 2010)
Indian Economy is one of the fastest growing economies in the world. The five years spanning 2003-04 and 2007-08 was an outstanding period of rapid growth. In this relatively short span of five years, average GDP growth was 8.8 per cent and per capital GDP increased by 7.2 per cent annually . GDP originating from the manufacturing sector averaged a creditable growth of 9 per cent. The industrial sector (including mining, electricity and utilities and construction) grew even faster, by 9.5 per cent.However, as economies grow richer, they demand more power and also pollute more. Increase in pollution levels over a period of time have lead to serious environmental hazards such as global warming, droughts, floods, extinction of species etc. The countries expected to experience the fastest growth in emissions are also those who are expected to have the most economic growth. The Stern report on climate change explains that developing countries, especially in the tropical and sub-tropical regions are expected to suffer most and soonest from climate change.